Controlled trial of immune response of preterm infants to recombinant hepatitis B and inactivated poliovirus vaccines administered simultaneously shortly after birth. Issue 1 (1st July 2000) - Linder, Nehama; Handsher, Rachel; German, Boris; Sirota, Lea; Bachman, Mike; Zinger, Sigal; Mendelson, Ella; Barzilai, Asher
Abstract : AIM: The study was conducted to evaluate the immunogenicity of an early, extra dose of enhanced inactivated poliovirus vaccine (IPV) administered simultaneously with recombinant hepatitis B vaccine (HBV) to preterm infants shortly after birth. METHODS: Three groups were studied. Fifty preterm infants received IPV intramuscularly within 24 hours of birth, in addition to routine recommended childhood immunisations. Fifty two preterm infants and 35 full term infants received routine immunisations only (routine vaccination timing: HBV at birth, 1 and 6 months of age; IPV at 2 and 4 months; oral polio vaccine (OPV) at 4 and 6 months; diphtheria-tetanus-pertussis (DTP) at 2, 4, and 6 months; and Haemophilus influenzae B vaccine at 2 and 4 months). Blood samples were taken at birth, 3 and 7 months of age from all infants, and at 1 month of age from preterm infants only. RESULTS: At birth, a lower percentage of both study and control preterm infants had antipoliovirus type 3 titres ⩾ 1:8 than full term infants. At 1 and 3 months of age significantly more early IPV infants had antipoliovirus type 3 titres ⩾ 1:8 than routinely vaccinated preterm infants (p < 0.05). At 7 months of age there were no significant differences in percentage of antipoliovirus titres ⩾ 1:8 or geometric mean times (GMTs) between the early IPV group and the routinely vaccinated preterm group. At 3 and 7 months of age, the percentage of positive antihepatitis B titres (⩾ 1:10) and the GMT of the early IPV preterm group did not differ significantly from those of preterm controls. There was no significant difference in percentage of positive antihepatitis B titres between the early IPV group and full term controls at any time. GMTs for hepatitis B antibodies were significantly lower in the early IPV preterm group than in full term controls at 3 and 7 months of age. CONCLUSIONS: Administration of an additional dose of IPV simultaneously with routine HBV to preterm infants shortly after birth provides early protection from poliovirus and hepatitis B infection, and does not interfere with poliovirus antibody production at the age of 7 months.